2015
DOI: 10.1016/j.biopsych.2014.06.024
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Ketamine-Induced Changes in [ 11 C]ABP688 Binding to Metabotropic Glutamate Receptor Subtype 5

Abstract: Background At subanesthetic doses, ketamine, an N-Methyl-D-aspartate (NMDA) glutamate receptor antagonist, increases glutamate release. Here, we imaged the acute effect of ketamine on brain metabotropic glutamatergic receptors subtype 5 (mGluR5) with a high affinity PET ligand [11C]ABP688 ((E)-3-((6-methylpyridin-2-yl)ethynyl)-cyclohex-2-enone-O-11C-methyl-oxime), a negative allosteric modulator of mGluR5. Methods Ten healthy nonsmoking human volunteers (34±13 years old) received two [11C]ABP688 PET scans on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
94
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(102 citation statements)
references
References 68 publications
6
94
1
1
Order By: Relevance
“…Since there are no readily available ligands for the NMDAR to allow PET imaging studies, alternative measures are needed. A recent paper suggests it may be possible to indirectly monitor ketamine's effects with the use of a PET ligand, [ 11 C]ABP688 (E)-3-[2-(6-methyl-2-pyridinyl)ethynyl]-2-cyclohexen-1-one-O-(methyl-11 C)oxime, that has high affinity for the mGluR5 receptor which is sensitive to changes in endogenous glutamate (DeLorenzo et al, 2014). Preclinical and small clinical studies suggest other imaging methods such as 13 C-MRS measures of glutamate cycling (Chowdhury et al, 2012), or fMRI studies of brain network connectivity could be used to evaluate target engagement, and perhaps may even be more closely related to the critical down stream mechanisms generating the antidepressant response (Dawson et al, 2014;Driesen et al, 2013).…”
Section: Novel Drug Developmentmentioning
confidence: 99%
“…Since there are no readily available ligands for the NMDAR to allow PET imaging studies, alternative measures are needed. A recent paper suggests it may be possible to indirectly monitor ketamine's effects with the use of a PET ligand, [ 11 C]ABP688 (E)-3-[2-(6-methyl-2-pyridinyl)ethynyl]-2-cyclohexen-1-one-O-(methyl-11 C)oxime, that has high affinity for the mGluR5 receptor which is sensitive to changes in endogenous glutamate (DeLorenzo et al, 2014). Preclinical and small clinical studies suggest other imaging methods such as 13 C-MRS measures of glutamate cycling (Chowdhury et al, 2012), or fMRI studies of brain network connectivity could be used to evaluate target engagement, and perhaps may even be more closely related to the critical down stream mechanisms generating the antidepressant response (Dawson et al, 2014;Driesen et al, 2013).…”
Section: Novel Drug Developmentmentioning
confidence: 99%
“…V T values were consistent with the known distribution of mGluR5 in humans, and the reliability of this parameter has been demonstrated (18,21), supporting its validity to quantify mGluR5 availability. Third, as suggested for another allosteric mGluR5 PET tracer (20), variation in extracellular glutamate levels could have affected findings. Here, we found no significant correlations between ACC glutamate/glutamine levels and tracer binding.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, given the suggested involvement of ACC glutamate concentrations in personality and their possible influence on mGluR5 availability (20), mGluR5 and temperament measures were related to spectroscopic measures of ACC glutamate-glutamine levels.…”
mentioning
confidence: 99%
“…Some investigators have reported that ketamine affects several neuronal transmission systems, such as dopamine receptor and transporter [43][44][45][46], serotonin receptor and transporter [47], glutamate receptor [48], etc. However, interference of ketamine with VMAT2, another important target in the central nervous system, which mediating monoaminergic transmission, is still unknown.…”
Section: Ketaminementioning
confidence: 99%